Hypogonadism and sexual function in men affected by adrenocortical carcinoma under mitotane therapy - Canu, Letizia; Sparano, Clotilde; Naletto, Lara; De Filpo, Giuseppina; Cantini, Giulia; Rapizzi, Elena; Martinelli, Serena; Ercolino, Tonino; Cioppi, Francesca; Fantoni, Alessandro; Zanatta, Lorenzo; Terreni, Alessandro; et al. (Frontiers in Endocrinology, 2024)
Purpose: Adrenocortical carcinoma (ACC) is a rare and aggressive tumor. ACC male patients under adjuvant mitotane therapy (AMT) frequently develop hypogonadism, however sexual function has never been assessed in this setting. The aim of this retrospective study was to evaluate in AMT treated ACC patients the changes in Luteinizing hormone (LH), Sex Hormone Binding Globulin (SHBG), total testosterone (TT) and calculated free testosterone (cFT), the prevalence and type of hypogonadism and sexual function, the latter before and after androgen replacement therapy (ART). Methods: LH, SHBG, TT and cFT were assessed in ten ACC patients at baseline (T0) and six (T1), twelve (T2), and eighteen (T3) months after AMT. At T3, ART was initiated in eight hypogonadal patients, and LH, SHBG, TT and cFT levels were evaluated after six months (T4). In six patients, sexual function was evaluated before (T3) and after (T4) ART using the International Index of Erectile Function-15 (IIEF-15) questionnaire. Results: Under AMT we observed higher SHBG and LH and lower cFT levels at T1-T3 compared to T0 (all p<0.05). At T3, hypergonadotropic hypogonadism and erectile dysfunction (ED) were detected in 80% and 83.3% of cases. At T4, we observed a significant cFT increase in men treated with T gel, and a significant improvement in IIEF-15 total and subdomains scores and ED prevalence (16.7%) in men under ART. Conclusions: AMT was associated with hypergonatropic hypogonadism and ED, while ART led to a significant improvement of cFT levels and sexual function in the hypogonadal ACC patients. Therefore, we suggest to evaluate LH, SHBG, TT and cFT and sexual function during AMT, and start ART in the hypogonadal ACC patients with sexual dysfunction.